Testing, Debugging, and Log Analysis With Modern AI Tools - Staron, Miroslaw; Abrahao, Silvia; Gay, Gregory; Serebrenik, Alexander; Abrahao, Silvia; Staron, Miroslaw (IEEE software, 2024)
This edition of the “Practitioners’ Digest” covers recent papers employing generative artificial intelligence in support of testing, debugging, and log analysis that were presented at the 38th IEEE/ACM International Conference on Automated Software Engineering (ASE 2023) and the 16th IEEE International Conference on Software, Testing, Verification and Validation (ICST 2023). Feedback or suggestions are welcome. In addition, if you try or adopt any of the practices included in the column, please send us and the authors of the paper(s) a note about your experiences.